Intravenous prostanoids in systemic sclerosis-associated pulmonary arterial hypertension: a single-centre experience. (17th June 2021) - Vlachou, Maria; Fayed, Hossam; Dawson, Adele; Reddecliffe, Sally; Stevenson, Alexander; Thomson, Ross J; Schreiber, Benjamin Emmanuel; Coghlan, J Gerry
Abstract: Objectives: The current study evaluates survival rates among SSc-associated pulmonary arterial hypertension (SSc-PAH) patients on i.v. prostanoids, and short-term impact of i.v. prostanoids on clinical and haemodynamic parameters. Methods: Baseline demographics, invasive and non-invasive data, European Society of Cardiology (ESC) score and REVEAL score of 81 SSc-PAH patients (median age 61 years, interquartile range 54–67 years, 84% females) were prospectively recorded, from November 2006 till November 2020, before initiation of i.v. prostanoids, and at first formal reassessment. Survival data were retrieved from National Health Service Spine and hospital databases. Results: Significant improvements in clinical and haemodynamic parameters in response to i.v. prostanoid therapy were documented. Functional class (FC) (16.6% improved by 1FC, P =0.041), mean pulmonary arterial pressure (−6.5 mmHg, P =0.036), pulmonary vascular resistance (−2.6 WU, P =0.012), cardiac index (Q/m 2 ) (+0.7 l/min/m 2, P =0.003) and mixed venous oxygen saturation (SvO2 ) (+3%, P =0.036) improved. Estimated survival for CTD-PAH patients on i.v. prostanoids was 64%, 31% and 18%, at 1 year, 3 years and 5 years, respectively. Independent baseline predictors of mortality were older age (HR: 1.043, 95% CI: 1.011–1.075, P =0.007), higher N-terminal pro-brain natriuretic peptide levels (HR: 2.191, 95% CI: 1.131–4.243, P =0.020), and lower SvO2 levels (HR: 0.962, 95% CI: 0.926–0.998, P =0.039). High ESC risk or high and very high REVEAL score was associated with significantly worse survival compared with patients with lower risk scores, both at baseline and when reassessed after a median of 6.5 months. Conclusions: Survival among SSc-PAH patients on i.v. prostanoids remains poor, risk scoring at baseline and after 6.5 months of therapy improves prognostication.